Políticas públicas e gestão educacional: distorção idade/ano na rede pública de educação no município de Santa Maria/RS - Chiapinoto, Andreia Moro (2022)
This Professional Master's research comes from the Graduate Program in Public Policy and Educational Management at the Federal University of Santa Maria. Its general objective is to understand the Public Policies related to the age/year distortion, as well as its implications in the correction of the school flow in elementary education in the Santa Maria/RS municipal education network. The following specific objectives were defined: survey age/year distortion rates and school performance indicators at national and municipal levels; to identify the factors that contribute to the occurrence of the age/year distortion in elementary school; to verify which public policies are proposed or adopted by the municipality of Santa Maria in order to reduce the age/year distortion rates; to prepare an illustrative and explanatory e-book on the data obtained in the research and disseminate it on the Network. It is based on a qualitative approach research (Minayo 2010 and Flick 2013), of the Yin case study type (2011), carried out in the municipal public education network of Santa Maria/RS. The research subjects were the managers of the municipal education department and also the managers of municipal schools. As research techniques, semi-structured interviews and online questionnaires were used. Data analysis was based on three categories and their subcategories: Public Policies – Preventive, Remedial, Intersectoral Actions; Factors – Intraschool, Extraschool, Coronavirus and Education; School trajectory – Concept of School Success, Non-Learning, Assessment. Thus, the age/year distortion rates have been decreasing by about one percentage point since 2006 in Brazilian public schools. It is pointed out that the age/year distortion in Elementary School is a complex issue, and they are related to public policies, family culture, issues of social vulnerability or more specific personal situations. In the municipality of Santa Maria, the public policy Connection of Knowledge stands out for being directly linked to the strategy of correcting school flow, based on two initiatives: one preventive and the other restorative. As it is a research linked to the Professional Master's, the educational product is an e-book on the topic age/year distortion and school flow correction in the municipality of Santa Maria. It is concluded that the researched subject still opens possibilities for the development of other investigations in greater depth or specificity, such as the hearing of students and/or family members who are in age/year distortion, their conceptions of education, life plans, among others. It is hoped that this research can contribute to overcoming the number of students with age/year distortion in elementary school in the municipality of Santa Maria/RS, allowing to qualify and optimize teaching, even interfering in the better use of public resources invested in education.